Pengaruh Tayangan Komedi Lapor Pak! terhadap Loyalitas Menonton Program di Trans7 - Ridwan Allam Zhafarry; Amin Shabana (Sekolah Tinggi Agama Buddha Nalanda, 2023)
One of the reality shows that recently appeared on Trans 7 is the Comedy Show Lapor Pak. The program stars well-known comedians in Indonesia, set in a police station and packed with comedy about criminal cases, current issues and celebrity gossip. A way of delivering that invites laughter for the audience. The aim of this research is to measure the comedy show Lapor Pak on Trans 7, viewing loyalty, and how much influence the comedy show Lapor Pak has on viewing loyalty. Sampling used Non Probability Sampling Technique with a sample of 89 people. The data analysis methods used in this research are validity testing, reliability testing, simple linear regression testing, and hypothesis testing. The results of the research show that the Comedy Show variable Report Pak! has a good score, this is based on the total calculated average value of 3.814. Then the variable Loyalty of watching has a good score, this is based on a total average value of 3.919. For a simple regression test, the result obtained is 0.624, which means the relationship or correlation between the variables Comedy Shows Report Sir! high or strong influence on the Watching Loyalty variable. For hypothesis testing, the results obtained were 1.663. calculated t value (3.893) > t table (1.663) then it can be concluded that H0 is rejected and H1 is accepted, which shows that there is an influence between the Comedy Show variable Report Sir! with the Watching Loyalty variable.